Effect of process parameter on microstructure and mechanical performance study of laser powder bed fusion processed 17-4 PH stainless steel under Argon gas atmosphere - Pok, Shu Rong (Nanyang Technological University, 2022)
Additive Manufacturing (AM), known as 3-D printing, is a modernize technology enables computer aided design (CAD) 3-dimension (3D) models into real functional parts. AM is a manufacturing process that enables production of functional parts from 3D models with near net shape condition. AM can be classified into two main categories. Powder bed (PB) and Flow-based techniques. Power bed technique consists of Electron Beam melting (EBM) and Selective Laser melting (SLM). Flow-based technique consists of laser-engineered net shaping (LENS), direct metal deposition (DMD) and direct metal laser sintering (DMLS). In this study, SLM is used to for fabricating of 17-4 PH Stainless steel. To obtain the optimal process parameter. 9 samples with different set of process parameter are fabricated to conduct the investigation on mechanical and microstructure properties. The objective of this study is to gain a deeper understanding of 17-4 PH stainless by investigating on the microstructure change with different process parameter and its relationships with mechanical property. The project will mainly focus on the porosity of 17-4 PH samples and its relationship with microstructure and mechanical properties, From mechanical analysis, microhardness test is conducted to investigate the highest hardness. Sample 1 and 2 can conclude to have a higher hardness as compared the sample 3 to 9. From microstructure analysis, optical microscopy analysis, sample 9 and 8 having the highest porosity can be seen as having the two worse porosity count with 12.39% and 0.78% respectively. Sample 9 having 2 orders of magnitude differences as compared to sample 1 to 8. Sample 9 is omitted for the rest of the analysis. Sample 1 to 7 having porosity percentage from 0.13 – 0.23% with overlap error bar, therefore no significant conclusion can be made. From Max Pore size, sample 2 and sample 6 having the lowest maximum pore size, with 87μm and 61μm. EDX analysis have been done for sample 1 and 8 to measure the oxygen content presence in the sample to test for gas porosity in the sample. However, limitation of EDX which unable to measure light elements deem unfit for this experiment. Chemical composition for sample 2 and 6 is consistent. XRD, Rietveld refinement analysis for sample 2 and 6 shows that retained austenite 3.7% and 0.3% respectively. In line with EBSD, sample 2 and 6 have 2.7% and 0.3% retained austenite respectively. With this study, it hopes to aid reader to understand properties of 17-4 PH stainless steel having high hardness and corrosion resistance at high temperatures (316 °C). Therefore, further improve its application in industries such as aerospace, automobile, biomedical, defence, marine, chemical, and petrochemical.